MODEL PEMBELAJARAN KOOPERATIF TIPE COOPERATIVE INTEGRADED READING AND COMPOSITION (CIRC) UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA - Muhsin Muhsin; Husna Husna (Jurnal Sains Riset, 2021)
Communication ability is one of the goals of school mathematics learning, which is to directstudents to be able to communicate problems in mathematics to explain situations or problems.One effort that can be done by teachers is to use the Cooperative Integrated Reading andComposition (CIRC) learning model. The subjects of this study were students of class VIII SMPNegeri 1 Padang Tiji. The purpose of this research is to find out whether the Cooperative Integrated Reading and Composition (CIRC) learning model can improve students' mathematicalcommunication skills. The population in this study was class VIII SMP Negeri 1 Padang Tiji,while the sample of this study was class VIII1 as the control class and class VIII3 as the experimental class. The sample of this study was selected using purposive sampling technique.Data collection methods used pre-test and post-test. Data analysis used the difference test of twomeans. The results showed that learning Cooperative Integrated Reading and Composition (CIRC)can improve students' mathematical communication skills. This is indicated by the calculation ofthe difference in the two averages obtained by the value of Asymp. Sig (1-tailed) 0.001 (0.05)then H0 is rejected, so H1 is accepted.